Perancangan Dan Implementasi Manajemen Jaringan Di Lingkungan Madrasah sanawiyah Yuppi Wonokerto - Dandi Ilham Pratama; Toibah Umi Kalsum; Yessi Mardiana (UNIVED Press, 2026)
Madrasah Tsanawiyah Yuppi Wonokerto, one of the schools in Lubuklinggau, currently has a computer laboratory to support teaching and learning activities. The computer network is equipped with internet access, and the laboratory facilities are used to support teaching and learning activities. With Network Management within Madrasah Tsanawiyah Yuppi Wonokerto, it is expected that the computer network at Madrasah Tsanawiyah Yuppi Wonokerto will improve and be more useful for teaching and learning activities. Network management at Madrasah Tsanawiyah Yuppi Wonokerto has resulted in a more structured network, allowing for more beneficial internet access, such as restricting access to websites unrelated to teaching and learning activities. The network management at Madrasah Tsanawiyah Yuppi Wonokerto utilizes a MikroTik router. MikroTik routers are excellent for network management, with resource usage being as low as 25%.